Lattice motions from THz phonon polaritons measured with femtosecond X-ray diffraction - Cavalleri, A; Wall, S; Rini, M; Simpson, C; Dean, N; Khalil, M; Statz, E; Ward, D; Nelson, K; Shoenlein, R (Optical Society of America, 2007)
We use femtosecond x-ray diffraction to measure the coherent lattice displacements associated with the excitation and propagation of THz phonon polaritons in LiTaO3.